'Global Britain': implications for UK military strategy and capability. Issue 7 (9th August 2021) - Unknown
Abstract : The United Kingdom released its Integrated Review of Security, Defence, Development and Foreign Policy in March 2021. The review calls for more British forces to be deployed globally and for longer periods – both within NATO and independently – for capacity-building missions and to actively counter terrorist, hybrid, grey-zone and proxy threats. It also sees the Royal Navy playing an important role in future conflicts and calls for increases in maritime capability and reductions in air- and land-based forces in favour of investments in advanced technology.